Economic justice in an unfair world toward a level playing field - Kapstein, Ethan B. (Princeton Princeton University Press, 2006)
Recent years have seen a growing number of activists, scholars, and even policymakers claiming that the global economy is unfair and unjust, particularly to developing countries and the poor within them. But what would a fair or just global economy look like? Economic Justice in an Unfair World seeks to answer that question by presenting a bold and provocative argument that emphasizes economic relations among states.
Includes bibliographical references (p. [197]-234) and index.
Keywords: Distributive justice